Search for heavy neutral leptons in final states with electrons, muons, and hadronically decaying tau leptons in proton-proton collisions at √s=13 TeV - Hayrapetyan, A. (2024)
A search for heavy neutral leptons (HNLs) of Majorana or Dirac type using proton-proton collision data at root s = 13TeV= 13 TeV is presented. The data were collected by the CMS experiment at the CERN LHC and correspond to an integrated luminosity of 138 fb(-1). Events with three charged leptons (electrons, muons, and hadronically decaying tau leptons) are selected, corresponding to HNL production in association with a charged lepton and decay of the HNL to two charged leptons and a standard model (SM) neutrino. The search is performed for HNL masses between 10 GeV and 1.5 TeV. No evidence for an HNL signal is observed in data. Upper limits at 95% confidence level are found for the squared coupling strength of the HNL to SM neutrinos, considering exclusive coupling of the HNL to a single SM neutrino generation, for both Majorana and Dirac HNLs. The limits exceed previously achieved experimental constraints for a wide range of HNL masses, and the limits on tau neutrino coupling scenarios with HNL masses above the W boson mass are presented for the first time.